2018
DOI: 10.1177/1369433218766941
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic investigation of layered graded metallic foams under dynamic compaction

Abstract: This article is aimed to reveal the dynamic response of layered graded metallic foam under impact loading using a three-dimensional mesoscopic model. First, a mesoscopic model for closed-cell metallic foam is proposed based on the X-ray computed tomography images. Second, a numerical analysis approach is presented and validated with test data. Third, it studies the dynamic behavior of the layered graded metallic foam under impact loading numerically. The metallic foam specimen is composed layer by layer. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It is challenging to calculate the effects of DC because of its dynamic characteristics. Therefore, recent research on DC has primarily focused on tests and simulations [2,[11][12][13]. For engineering design or control aspects, a simple calculation method is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…It is challenging to calculate the effects of DC because of its dynamic characteristics. Therefore, recent research on DC has primarily focused on tests and simulations [2,[11][12][13]. For engineering design or control aspects, a simple calculation method is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete structures are more likely to be destroyed under the dynamic load, and the casualties and property losses are also more serious [4,5]. To make concrete structures safe, some scholars have researched improving the dynamic mechanical properties of concrete structures [6][7][8]. It has been shown that metal foams with good impact resistance [9,10] are often used as a protective layer of structures.…”
Section: Introductionmentioning
confidence: 99%
“…25 Most of the previous studies have focused on the introduction of a proprietary gradient that can vary the general response of FGM structures with certain optimization of the arrangement of the gradient profiles. From a theoretical study's perspective, some constitutive models have recently been reported in the literature to model the behavior of layered graded foams under quasi-static and impact loading, such as the mesoscopic model; 26 shock model; 27 elastic, collapse, plastic-hardening, densification constitutive model; 28 and elastic, plastic-hardening, locking model. 29 The aim of this study is to provide insights into the impact perforation of sandwich panels made of 0.8 mm 2024-T3 aluminum alloy skin sheets and graded polymeric hollow sphere cores.…”
Section: Introductionmentioning
confidence: 99%